PENDIDIKAN DAN PELATIHAN PEGAWAI SEBAGAI FAKTOR KUNCI KEBERHASILAN PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DALAM PENCAPAIAN INDIKATOR NASIONAL MUTU (INM) DI RSGMP X - Wigati, Putri Asmita; Fatmasari, Eka Yunila (Jurnal Manajemen Kesehatan Indonesia, 2024)
National Quality Indicators (INM) at RSGMP X in Semarang haves not reached the target in the aspect of 6-step handwashing compliance and the use of personal protective equipment among doctors, nurses and young dentists. Other research has found that education and training for employees is important in improving their technical skills and professional expertise. This study aims to determine the relationship between education and training as one of the elements of TQM and the achievement of INM at RSGMP X in Semarang City. This study is an observational quantitative study with a cross sectional approach. Data collection using a questionnaire by google form with a total sample of 75 of employee. Data analysis was performed bivariately with chi square. There is a relationship between perceptions of education and training aspects and the achievement of INM at RSGMP X in Semarang City. In addition, respondents who have good perceptions of education and training aspects tend to support the achievement of good INM (57.3%) compared to those who are not good (25.3%). Respondents with unfavorable perceptions of education and training tended to be less supportive of INM achievement (12%) compared to those who were supportive of INM achievement (5.4%). Most of the study respondents had good perceptions on education and training aspects (82.6%). In improving the achievement of National Quality Indicators, hospitals need to emphasize education and training efforts.Keywords : TQM, National Quality Indicators, Indikator Nasional Mutu, Education, Training